2015
DOI: 10.1111/aos.12913
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter clinical trial of high‐intensity focused ultrasound treatment in glaucoma patients without previous filtering surgery

Abstract: ABSTRACT.Purpose: To evaluate the efficacy and safety of the ultrasonic circular cyclocoagulation procedure in patients with open-angle glaucoma na€ ıve of previous filtering surgery. Methods: Prospective non-comparative interventional clinical study conducted in five French University Hospitals. Thirty eyes of 30 patients with open-angle glaucoma, intra-ocular pressure (IOP) > 21 mmHg and with no previous filtering glaucoma surgeries were sonicated with a probe comprising six piezoelectric transducers. The si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
54
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 36 publications
9
54
1
3
Order By: Relevance
“…A hypothetical model could be proposed to explain the causes of the failures according to the timeframe of their onset: early failures may reflect an insufficient amount of ciliary body tissue coagulated during the procedure [19], while late failures may reflect the possible re-epithelialization of the ciliary processes with the progressive recovery of their function [21,22], or the gradual narrowing of the stimulated uveoscleral outflow pathway [7,9,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hypothetical model could be proposed to explain the causes of the failures according to the timeframe of their onset: early failures may reflect an insufficient amount of ciliary body tissue coagulated during the procedure [19], while late failures may reflect the possible re-epithelialization of the ciliary processes with the progressive recovery of their function [21,22], or the gradual narrowing of the stimulated uveoscleral outflow pathway [7,9,15].…”
Section: Discussionmentioning
confidence: 99%
“…Other additional limitations include the inhomogeneous patient characteristics which reflect a realworld glaucoma population, and the use of success criteria different from the World Glaucoma Association criteria [23] in order to conduct a more reliable comparison with the existing literature [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, preoperative IOP ranged from 27.5 to 39.1 mmHg, whereas postoperative IOP ranged from 17.1 to 23 mmHg at the last follow-up [1618, 21, 88, 89]. …”
Section: Miniaturized High-intensity Focused Ultrasounds For Cyclomentioning
confidence: 99%
“…The mean number of the UC 3 procedure in the first 12 months ranged from 1.05 to 1.13 in the study of Aptel et al, while Denis et al reported percentages of retreatment from 17.6 to 29.4% in the 6- and 4-second dose regimens, respectively [17, 89]. Finally, all these studies did not report a significant reduction of the mean number of medications after the procedure, especially in the long-term studies.…”
Section: Miniaturized High-intensity Focused Ultrasounds For Cyclomentioning
confidence: 99%
See 1 more Smart Citation